The Effect Of Low Impact Aerobic Exercise On Lowering Blood Pressure In Prolanis Members With Hypertension - Arian, Pipit Puspita (Jurnal Health Society, 2024)
Introduction: Hypertension is a chronic degenerative disease due to disorders of the circulatory system is still a public health problem. Low Impact Aerobic Exercise for Prolanis Members is a non-pharmacological effort to overcome hypertension. If there is a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg, it is called hypertension. The purpose of this study was to determine the effect of low impact aerobic exercise on blood pressure reduction. Method: The design of this study is a quasi-experiment with a pre-and pos-test design. The sample was 17 people, using purposive sampling technique. Data collection methods using a questionnaire. Data analysis was carried out by looking at the description of the characteristics of respondents, univariate analysis and bivariate analysis using the Wolcoxon test. Results: The results of the bivariate test obtained a p-value of 0.000 showed that there was an effect of Low Impact Aerobic exercise with a decrease in blood pressure. Conclusion: The conclusion in this study is that there is an effect of Low Impact Aerobic exercise with a decrease in blood pressure. It is hoped that the results of this study can provide information and become an alternative to the Puskesmas sports health program for outside prolanis to be able to continue Aerobic Low Impact exercises in other hypertensive patients.